Current Perspectives on Idiopathic Intracranial Hypertension without Papilloedema - Susan P. Mollan; Yu Jeat Chong; Olivia Grech; Alex J. Sinclair; Benjamin R. Wakerley (Life, 2021)
The pseudotumor cerebri syndrome embraces disorders characterised by raised intracranial pressure, where the commonest symptom is headache (90%). Idiopathic intracranial hypertension without papilloedema (IIHWOP) is increasingly recognised as a source of refractory headache symptoms and resultant neurological disability. Although the majority of patients with IIHWOP are phenotypically similar to those with idiopathic intracranial hypertension (IIH), it remains uncertain as to whether IIHWOP is nosologically distinct from IIH. The incidence, prevalence, and the degree of association with the world-wide obesity epidemic is unknown. Establishing a diagnosis of IIHWOP can be challenging, as often lumbar puncture is not routinely part of the work-up for refractory headaches. There are published diagnostic criteria for IIHWOP; however, some report uncertainty regarding a pathologically acceptable cut off for a raised lumbar puncture opening pressure, which is a key criterion. The literature provides little information to help guide clinicians in managing patients with IIHWOP. Further research is therefore needed to better understand the mechanisms that drive the development of chronic daily headaches and a relationship to intracranial pressure; and indeed, whether such patients would benefit from therapies to lower intracranial pressure. The aim of this narrative review was to perform a detailed search of the scientific literature and provide a summary of historic and current opinion regarding IIHWOP.